Modelling polymer draft gears. Issue 9 (1st September 2016) - Wu, Qing; Yang, Xiangjian; Cole, Colin; Luo, Shihui
ABSTRACT: This paper developed a new and simple approach to model polymer draft gears. Two types of polymer draft gears were modelled and compared with experimental data. Impact characteristics, in-train characteristics and frequency responses of these polymer draft gears were studied and compared with those of a friction draft gear. The impact simulations show that polymer draft gears can withstand higher impact speeds than the friction draft gear. Longitudinal train dynamics simulations show that polymer draft gears have significantly longer deflections than friction draft gears in normal train operations. The maximum draft gear working velocities are lower than 0.2 m/s, which are significantly lower than the impact velocities during shunting operations. Draft gears' in-train characteristics are similar to their static characteristics but are very different from their impact characteristics; this conclusion has also been reached from frequency response simulations. An analysis of gangway bridge plate failures was also conducted and it was found that they were caused by coupler angling behaviour and long draft gear deflections.